2011
DOI: 10.1002/mc.20862
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic associations of circadian gene TIMELESS and breast cancer risk

Abstract: Results from recent molecular epidemiologic studies suggest that the core circadian genes play a role in breast tumorigenesis, possibly by influencing hormone regulation or other pathways relevant to cancer. In order to further evaluate this hypothesis, we conducted a genetic and epigenetic association study of the circadian regulator TIMELESS in breast carcinogenesis. We detected significant associations between two tagging SNPs (rs2291738 and rs7302060) in the TIMELESS gene and breast cancer among 441 breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 18 publications
5
48
0
Order By: Relevance
“…While altered expressions of TIMELESS and DLX1 have been reported for a variety of cancers,2021222324 they have not been associated with prostate cancer metastasis. The elevated expression of TIMELESS found in our metastatic xenografts ( Table 1 ), as well as in metastatic prostate cancer patients’ samples (MSKCC cohort; Figure 2a ) and a strong correlation between elevated TIMELESS expression and poor clinical patients’ outcome (increased seminal vesicle invasion and lymph node involvement; Figure 2b ), suggest that this gene has a role in prostate cancer metastasis and perhaps as a metastasis-driving gene.…”
Section: Discussionmentioning
confidence: 90%
“…While altered expressions of TIMELESS and DLX1 have been reported for a variety of cancers,2021222324 they have not been associated with prostate cancer metastasis. The elevated expression of TIMELESS found in our metastatic xenografts ( Table 1 ), as well as in metastatic prostate cancer patients’ samples (MSKCC cohort; Figure 2a ) and a strong correlation between elevated TIMELESS expression and poor clinical patients’ outcome (increased seminal vesicle invasion and lymph node involvement; Figure 2b ), suggest that this gene has a role in prostate cancer metastasis and perhaps as a metastasis-driving gene.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies also reported that variants in NPAS2 (Zhu et al 2008), CRY2 (Hoffman et al 2010b,c), TIMELESS (Fu et al 2012), and ARNTL (BMAL1) (Zienolddiny et al 2013) were associated with breast cancer. These associations were study specific and were not replicated in our data.…”
Section: Main Genetic Effectsmentioning
confidence: 83%
“…Nonetheless, a lack of standardization for these potential differences represents a study uncertainty. 36,82,83 Other studies that targeted clock genes in PBLs indicated that DNA hypomethylation was associated with breast cancer diagnoses ( CLOCK ), 84 or with advanced stage (II-IV) breast cancer ( TIMELESS ), 85 whereas promoter hypermethylation was associated with postmenopausal breast cancer ( CRY2 ), 86 and with chronic myeloid leukemia ( PER3 ) 68 relative to controls. The mechanism through which PER1 or PER3 gene methylation may impact adenoma formation is unknown and may depend on tissue context, timing of expression relative to other cellular processes, location of epigenetic changes within the gene, or other factors that may disrupt clock gene expression, such as shift work.…”
Section: Discussionmentioning
confidence: 99%